2021
DOI: 10.1158/1078-0432.ccr-20-2246
|View full text |Cite
|
Sign up to set email alerts
|

Exploiting Protein Translation Dependence in Multiple Myeloma with Omacetaxine-Based Therapy

Abstract: Purpose:The prognosis of patients with multiple myeloma who are resistant to proteasome inhibitors, immunomodulatory drugs (IMiD), and daratumumab is extremely poor. Even B-cell maturation antigen–specific chimeric antigen receptor T-cell therapies provide only a temporary benefit before patients succumb to their disease. In this article, we interrogate the unique sensitivity of multiple myeloma cells to the alternative strategy of blocking protein translation with omacetaxine.Experimental Design:We determined… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 46 publications
2
6
0
Order By: Relevance
“… 55 , 56 Translational initiation inhibitors rocaglates and omacetaxine have been shown to suppress MM cell proliferation and induce cell death. 54 , 57 In line with these findings, we show that the combination of CX-5461 with panobinostat produced a double hit on ribosome biogenesis and mRNA translation in MM cells. Altogether, our findings support the feasibility of targeting the ribosome as an effective strategy to treat RRMM.…”
Section: Discussionsupporting
confidence: 82%
“… 55 , 56 Translational initiation inhibitors rocaglates and omacetaxine have been shown to suppress MM cell proliferation and induce cell death. 54 , 57 In line with these findings, we show that the combination of CX-5461 with panobinostat produced a double hit on ribosome biogenesis and mRNA translation in MM cells. Altogether, our findings support the feasibility of targeting the ribosome as an effective strategy to treat RRMM.…”
Section: Discussionsupporting
confidence: 82%
“…These cell lines are referred to herein as H929-OR (Omacetaxine Resistant) and MM1S-OR. Previously, we found that baseline protein synthesis rate correlated with ex vivo omacetaxine response in primary MM samples (7). OP-puromycin staining of omacetaxine-resistant cells revealed a significant decrease in H929-OR cells, and an increase in a subpopulation of MM1S-OR (Supplemental Fig.…”
Section: Resultsmentioning
confidence: 88%
“…As drug combinations are more efficacious than single agents in the treatment of MM, development of new drug combinations is of particular interest, especially those that include multiple new agents that the malignant cells have not been exposed to previously. The protein synthesis inhibitor omacetaxine is a promising new backbone therapy that we have shown retains activity in multiply relapsed patients (7). The goal of this study was to better understand how MM cells respond to prolonged omacetaxine exposure and how future patients may develop resistance to this therapy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…AKT-mediated sustained eIF4E expression and C/EBP translation have been proposed as the resistant mechanisms for IMiDs [ 61 ]. Moreover, the resistant mechanisms for current standard therapeutics for MM include aberrant MYC overexpression [ 50 ], and the increased rate of protein translation [ 62 ]. Considering these, one of the clinical positions of the dual-targeting therapy for RSK2 and AKT may be theoretically the salvage setting after treatment failure of PIs, and/or IMiDs with or without monoclonal antibodies for CD38 or SLAMF-7.…”
Section: Discussionmentioning
confidence: 99%